Key Management For Multicast Security - Daw, Win Aye (2005)
This thesis investigates and analyzes each of the group key management architectures, looking in particular at their scalability and security, since multicast scalability and security are the primary motivator for this work. Our domain problem is the key management for multicast security over wired and wireless networks to enhance the scalability and security for key distribution in the presence of member dynamics and to improve the algorithms for key generation.